IMPLEMENTASI AUGMENTED REALITY SEBAGAI MEDIA PENGENALAN AKSARA ARAB MELAYU BERBASIS ANDROID - Hussudur, Aldie Misbah; Pangaribuan, Hotma (Computer Science and Industrial Engineering, 2023)
Indonesia's diverse cultural heritage includes regional scripts and traditional writings, which currently face the risk of extinction due to limited data and declining use as a means of communication. Introducing the Arab-Malay script has mainly relied on print media, making it less appealing to the millennial generation, who prefer modern technology. This script holds cultural significance, originating from Riau Province and spreading across Indonesia, necessitating preservation for future generations. Augmented Reality (AR) technology is proposed as a solution, integrating 3D computer graphics with the real world to introduce and conserve the Arab-Malay script's richness. Using Unity and the Vuforia library, an AR application can project script images into the real environment using markers and Android smartphones, facilitating easier learning and engagement for younger generations in preserving this heritage.